Keragaman dan Kelimpahan Populasi Parasitoid Telur yang Berasosiasi dengan Hama Penggerek Batang Padi Kuning pada Pertanaman Padi di Kabupaten Tabanan - LATIZIO BENI DA COSTA CRUZ; I WAYAN SUPARTHA; NI NENGAH DARMIATI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2016)
The Diversity and Abundance of Egg Parasitoids Population that Associated with YellowRice Stem Borer on Rice Crop in Tabanan Regency. Rice stem borer is an important pest in rice plants that are real may cause decrease in result. Control of the rice stem borer in Tabanan still relies on the use of synthetic insecticides. This way is not effective. To overcome the problem it, necessary the efforts to integrated pest management. Biological control using the egg parasitoid rated as excellent because parasite as eggs of pests, so that pests do not develop into larvae (phases that damage crops). This research conducted in the sub district of Kediri which has a height (350 m asl) and in the sub district Baturiti which has a height (600 m asl) by using the survey method. The result showed that diversity of the population of parasitoid eggs rice stem borer yellow in both height appertain is low with diversity index <1.5. There are three species of parasitoid eggs found scilicet T. schoenobii, T. rowani T. japonicum with similarity index of 100% in the second location. Population abundance egg parasitoid in altitude (350 meters asl) highest is indicated by T. rowani and the lowest is shown by T. japonicum, while at altitude (600 m asl) highest is indicated by T.schoenobii and lowest shown T. japonicum. The level of parasitism parasitoid eggs have in common in both height. The highest level parasitism on the vegetative phase shown by T. schoenobii and on generative phase shown by T. rowani.